Electrospraying assisted by pressurized gas as an innovative high-throughput process for the microencapsulation and stabilization of docosahexaenoic acid-enriched fish oil in zein prolamine. (January 2019) - Busolo, M.A.; Torres-Giner, S.; Prieto, C.; Lagaron, J.M.
Abstract: Zein, a prolamine obtained from maize, was employed to encapsulate a fish oil highly enriched with docosahexaenoic acid (DHA) by an innovative process termed electrospraying assisted by pressurized gas (EAPG). This technology combines high electric voltage with pneumatic spray to yield a high-throughput encapsulation process. Semi-spherical zein flowable capsules with mean sizes of 1.4 μm containing the DHA-enriched fish oil were produced by EAPG from inert ethanol solutions at room conditions, presenting a high encapsulation efficiency. The oxidative stability tests carried out in the zein microcapsules obtained by EAPG showed that the DHA-enriched fish oil was efficiently protected over storage time. Sensory tests were also performed on fortified reconstituted milk with the freshly prepared zein/DHA-enriched fish oil microcapsules, suggesting negligible oxidation effects after 45 days. The results described herein indicate that EAPG is a promising innovative high-throughput electrospraying-based methodology for the encapsulation of bioactives and, therefore, the resultant DHA-enriched fish oil containing microcapsules can be industrially applied for the formulation of fortified foods. Industrial relevance: An innovative process, termed electrospraying assisted by pressurized gas (EAPG), is herein originally presented as a novel encapsulation methodology. This technology is based on the combination of high voltage and pneumatic spray, allowing the formation of microcapsules at room temperature conditions. Thus, EAPG shows a great deal of potential to encapsulate nutraceuticals and other bioactives that are sensitive to thermal degradation and/or oxidation. The resultant bioactive-containing capsules can be, thereafter, applied to develop novel fortified food products.